Stolzman w Belwederze? Instrumentalizacja antysemityzmu w kampaniach prezydenckich w Polsce po roku 1989 - Forecki, Piotr (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The Jewish presence is not indispensable for the anti-Semitic discourse to justify and legitimize its existence. This discourse fights against imaginary and symbolic Jews, those who are appointed to be Jewish, and in particular against everything that this discourse opposes and tries to associate with the Jews in all manners. Such practices have been implemented numerous times during the presidential election campaigns in Poland after 1989. However, the consequences of the instrumentalization of anti-Semitism, although deserving to be despised, should be neither overestimated nor exaggerated when interpreting the voters’ decisions. Were anti-Semitism the instrument of utmost influence indeed, Aleksander Kwaoeniewski would not have been elected Polish president twice.